Methylmercury myotoxicity targets formation of the myotendinous junction. (October 2020) - Peppriell, Ashley E.; Gunderson, Jakob T.; Vorojeikina, Daria; Rand, Matthew D.
Graphical abstract: Highlights: Methylmercury (MeHg) perturbs muscle development in Drosophila melanogaster . Developmental exposure to MeHg impairs eclosion and flight behaviors. MeHg perturbs flight muscle morphology by disrupting the myotendinous junction. Gene expression of the NG2/CSPG4 homologue, kon-tiki, is elevated by MeHg. Targeted overexpression of kon-tiki in muscle phenocopies MeHg effects. Abstract: Methylmercury (MeHg) is a ubiquitous environmental contaminant and developmental toxicant known to cause a variety of persistent motor and cognitive deficits. While previous research has focused predominantly on neurotoxic MeHg effects, emerging evidence points to a myotoxic role whereby MeHg induces defects in muscle development and maintenance. A genome wide association study for developmental sensitivity to MeHg in Drosophila has revealed several conserved muscle morphogenesis candidate genes that function in an array of processes from myoblast migration and fusion to myotendinous junction (MTJ) formation and myofibrillogenesis. Here, we investigated candidates for a role in mediating MeHg disruption of muscle development by evaluating morphological and functional phenotypes of the indirect flight muscles (IFMs) in pupal and adult flies following 0, 5, 10, and 15 μM MeHg exposure via feeding at the larval stage. Developmental MeHg exposure induced a dose-dependent increase in muscle detachments (myospheres) within dorsal bundles of the IFMs, which paralleled reductions eclosion and adult flight behaviors. These effects were selectively phenocopied by altered expression of kon-tiki ( kon ), a chondroitin sulfate proteoglycan 4/NG2 homologue and a central component of MTJ formation. MeHg elevated kon transcript expression at a crucial window of IFM development and transgene overexpression of kon could also phenocopy myosphere phenotypes and eclosion and flight deficits. Finally, the myosphere phenotype resulting from 10 μM MeHg was partially rescued in a background of reduced kon expression using a targeted RNAi approach. Our findings implicate a component of the MTJ as a MeHg toxicity target which broaden the understanding of how motor deficits can emerge from early life MeHg exposure.